Vitamin C in-vivo Effect on Liver Enzymes and Some Endogenous Antioxidants in Paracetamol-Induced Model of Liver Toxicity on Wistar Rats - E.G. Moke; K.K. Anachuna; P.O. Onyilo; M. Emosivbe (Journal of Applied Sciences and Environmental Management)
This study aimed at assessing the in-vivo effect of Vitamin C on liver enzymes and some endogenous antioxidants in paracetamol-induced model of liver toxicity on Wistar rats. The rats were grouped into four groups of five animals each; groups 1 and 2 were control (positive and negative), while group 3 and 4 received vitamin C 500 mg/kg and silymarin 100 mg/kg respectively. Dosing was oral and daily for 6 days according to their body weights. All the animals except the positive control group (Group 1) were administered paracetamol 3 g/kg on the 7th day, and then observed for 24 hours before sample collection for biochemical indices and liver histological studies. Paracetamol caused a significant (p<0.05) increase in liver enzymes, significant (p<0.05) decrease in antioxidant enzymes, and necrosis in liver tissues when compared to the control. Administration of 500 mg/kg Vitamin C prior to induction of liver damage by PCM resulted in significant (p<0.05) decreased liver enzyme and well as an increase in the antioxidant enzymes. Pre-treatment of the animals with vitamin C showed a reversal of the toxic effect of paracetamol on the rats.